Successful Achievement of Demanding Outcomes in Upadacitinib-Treated Atopic Dermatitis Patients: A Real-World, 96-Week Single-Centre Study - Stamatios Gregoriou; Ioannis-Alexios Koumprentziotis; Ileana Afroditi Kleidona; Michail Bakakis; Eleni Hatzidimitriou; Theodora Douvali; Aikaterini Tsiogka; Styliani Mastraftsi; Aristeidis Vaiopoulos; Alexander Stratigos (Dermatology and Therapy)
Abstract Introduction Results from randomized controlled trials of upadacitinib, a Janus kinase (JAK) inhibitor, have led to its approval for the treatment of moderate-to-severe atopic dermatitis (AD) in patients aged ≥ 12 years. The aim of this study was to report the effectiveness and safety of upadacitinib in real-world settings over a period of 96 weeks. Methods This retrospective study included all patients treated with upadacitinib at our centre between April 2022 and September 2024. Clinical and patient-reported outcomes were recorded and assessed at each follow-up visit and included the eczema area severity index (EASI), investigator global assessment (IGA), scoring atopic dermatitis (SCORAD), dermatology life quality index (DLQI) and the worst pruritus numerical scale score (WP-NRS). All drug-related adverse events (AEs) were documented. Results In total, 36 patients (44.4% female) were retrospectively included. After 4 weeks of treatment, the mean EASI was reduced from 29.97 to 3.72 with 83.3/52.8/19.4% achieving EASI75/90/100 respectively. Similar reductions were observed in the DLQI, which was reduced from 20.78 to 2.92, and in the WP-NRS, from 7.78 to 1.31. Further improvements were observed at week 16, with a mean EASI of 0.75 and 96.4% of the patients achieving EASI75 and EASI90. At week 48 of treatment, EASI75/90/100 were achieved by 100/93.8/81.3% along with a mean DLQI and pruritus NRS of 0.81. All nine patients that reached the 72- and 96-week timepoints had clear skin with no pruritus. Six (16.7%) patients experienced AEs with four of them discontinuing medication; no patient discontinued because of upadacitinib inefficacy. Conclusion This long-term real-world study of patients with moderate-to-severe AD receiving upadacitinib demonstrated that treatment success (EASI75/90/100) can be achieved in a high proportion of patients by week 16 and can be maintained for up to 96 weeks along with substantial improvements in pruritus and quality of life.